Answer:
a = 1
b = 2
k = -2
Explanation:
Given:
![\displaystyle \large{y=k(x-a)^2(x-b)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/4rwdmnfxl9cc8vvx85qmww0qcmq8f5aiv4.png)
First, find the a-value and b-value by observing the graph. Notice that once the graph hits x = 1, it just goes up or concave up - that indicates to be the double roots of function. Therefore:
Our a-value is 1
Second, find the b-value. Another x-intercept beside double roots x = 1 is x = 2 as shown in the graph. Therefore:
Our b-value is 2
Third, find the k-value. Right now we have the equation:
![\displaystyle \large{y=k(x-1)^2(x-2)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/641zito7x84l8a9rcwsmjlm3s1d08zr1ll.png)
To find the k-value, simply find a point’s value (x,y) to substitute. According to the graph, you can try substitute (0,4) in:
![\displaystyle \large{4=k(0-1)^2(0-2)}\\\displaystyle \large{4=k(-1)^2(-2)}\\\displaystyle \large{4=k(1)(-2)}\\\displaystyle \large{4=-2k}\\\displaystyle \large{k=-2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/h68j50c13dyyhmbr7mrmcghrramq82kauo.png)
Therefore, the value of k is -2